2016
DOI: 10.1016/j.cellsig.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of inositol hexakisphosphate kinase 1 (IP6K1) reduces cell migration and invasion, conferring protection from aerodigestive tract carcinoma in mice

Abstract: Inositol hexakisphosphate kinases (IP6Ks), a family of enzymes found in all eukaryotes, are responsible for the synthesis of 5-diphosphoinositol pentakisphosphate (5-IP7) from inositol hexakisphosphate (IP6). Three isoforms of IP6Ks are found in mammals, and gene deletions of each isoform lead to diverse, non-overlapping phenotypes in mice. Previous studies show a facilitatory role for IP6K2 in cell migration and invasion, properties that are essential for the early stages of tumorigenesis. However, IP6K2 also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 52 publications
4
56
0
Order By: Relevance
“…Deletion of Ip6k1 significantly influences various aspects of mouse biology, and thus, targeting this isoform is expected to be beneficial in obesity, T2D (45,58,69,70), innate immunity (59), thromboembolism (71), cancer metastasis (56), and psychiatric and neurodegenerative diseases (49). Ip6k1 KO mice are protected against high-fat diet-induced (HFD-induced) weight gain, insulin resistance, and fatty liver (58).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of Ip6k1 significantly influences various aspects of mouse biology, and thus, targeting this isoform is expected to be beneficial in obesity, T2D (45,58,69,70), innate immunity (59), thromboembolism (71), cancer metastasis (56), and psychiatric and neurodegenerative diseases (49). Ip6k1 KO mice are protected against high-fat diet-induced (HFD-induced) weight gain, insulin resistance, and fatty liver (58).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, IP6Ks exhibit distinct cellular functions (45,54). IP6K1-generated 5-IP7 modulates cell metabolism, signaling, exocytosis, and migration (48,(55)(56)(57)(58). IP6K1-generated 5-IP7 regulates insulin signaling by inhibiting the insulin-sensitizing protein kinase Akt both in vivo and in vitro (58)(59)(60)(61), whereas it promotes insulin secretion from pancreatic β cells (57).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shed light on the role of IP 7 in the promotion of tumour growth and metastasis using in vitro and in vivo approaches. 107,108 The Snyder group showed that gene deletion of Ip6k2 in HCT116 human colorectal cancer cells and Ip6k2 knockdown in breast and lung cancer cell lines led to a reduction in focal adhesion kinase (FAK) phosphorylation, correlating with reduced cell spreading and cell-matrix adhesion. 107 Epithelial to mesenchymal transition properties including cell migration and invasion were also significantly reduced in these cells.…”
Section: Actin Cytoskeletonmentioning
confidence: 99%
“…Recent work from our laboratory showed that IP6K1 also promotes cell migration and invasion. 108 Knockdown of IP6K1 expression in cancer cells leads to a reduction in cell migration, invasion and anchorage-independent growth. Ip6k1 knockout mice fed with the oral carcinogen 4NQO showed reduced progression from epithelial dysplasia to invasive carcinoma in the upper aerodigestive tract as compared with their wildtype littermates, showing that IP6K1 is also required to promote cell invasion in vivo.…”
Section: Actin Cytoskeletonmentioning
confidence: 99%
“…Amplification or constitutive hyperactivation (~10-50-fold) [239,240] of Akt causes tumorigenesis in vivo [241], whereas no tumors are formed when these conditions are not met [241]. Notably, a 2-3-fold increase in Akt activation improves metabolic functions [12,22] without forming tumors [242] in Ip6k1-KO mice. Moreover, Ip6k1-KO mice are protected from tumorigenesis and metastasis [242].…”
Section: Potential Risks Of Targeting the Ip6k Pathway In Metabolic Dmentioning
confidence: 99%